Real-World Analysis of Short-Term Effectiveness of Oral Semaglutide: Impact on Glycometabolic Control and Cardiovascular Risk - Sara Palazzi; Federica Sentinelli; Antonella Zugaro; Sara Morgante; Livia Santarelli; Sandra Melanzi; Annamaria De Mutiis; Deamaria Piersanti; Barbara Macerola; Marco Iezzi; Pietro Mercuri; Alessandro Ferranti; et al. (Pharmaceuticals)
Background: Oral semaglutide, a GLP1-receptor agonist (GLP1-RA), shows promise in efficacy and compliance, especially amid the global shortage of injectable GLP-1 RAs. Its short-term effectiveness remains unexplored. Objective: This real-world observational study assessed the short-term effectiveness of oral semaglutide after three months of therapy. Methods: Patients with type 2 diabetes from four Italian diabetes centers, who received an initial prescription of oral semaglutide, were reassessed after three months. Primary outcomes included glycated hemoglobin (HbA1c) and body weight reduction; secondary outcomes involved changes in lipid parameters and cardiovascular risk. Results: Among 167 participants (mean age 66.5 years, mostly obese, baseline HbA1c 8.4% ± 1.5), 83.2% received a 7 mg dose. After three months, HbA1c significantly declined (8.4% to 7.1%, −1.3%, p < 0.001), alongside body mass index (BMI) (30.9 kg/m2 to 29.6 kg/m2, p < 0.0001). The target HbA1c ≤ 7% was achieved by 54.5%, and 34.7% reached ≤6.5%. Patients losing >5% of their initial weight (30.5%) saw the largest HbA1c drop (−1.9%). Those with newly diagnosed diabetes or a duration < 5 years showed superior responses (p = 0.001), while no significant differences were found based on the timing of drug administration. Oral semaglutide replaced or supplemented prior therapies, allowing discontinuation of dipeptidyl peptidase 4 inhibitors (DPP4i), sulfonylureas, glinides, and acarbose, and deprescription of thiazolidinediones. A significant reduction in cardiovascular risk was observed (p = 0.04), together with a significant reduction in lipid parameters. Conclusions: Oral semaglutide showed significant short-term efficacy, reducing HbA1c, body weight, and cardiovascular risk in three months, making it a valuable therapeutic option.